Structural and frequency characteristics of archaisms in the language of Kazhygumar Shabdanuly’s six-volume novel "Kylmys" - Mursal, А.; Amirbekova, А.; Almautova, Ә. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
The article provides a comprehensive analysis of the structural and frequency features of old bookish vocabulary and archaisms in Qazhygumar Shabdanuly’s six-volume novel Qylmys (The Crime). The lexical units found in the text are examined with regard to their historical-semantic features, linguistic nature, and functional roles. The study outlines the theoretical foundations of old bookish vocabulary and its place within the Turkic written tradition. On this basis, the author’s religious, ethical, administrative, and everyday lexical layers are identified and grouped structurally. The obsolete units are compared with their modern equivalents in contemporary Kazakh. Special attention is devoted to the frequency of Arabic-Persian religious vocabulary, its contextual functions, and semantic nuances. Eight analytical tables were compiled to document the meanings and frequencies of these items, providing insight into the author’s linguistic choices. The findings enhance understanding of how historical lexical elements function within the narrative, revealing their frequency patterns and stylistic value. The study refines the semantic scope and contextual features of old bookish vocabulary and contributes to the systematization of the historical lexical corpus. Overall, the results shed light on the author’s motivations in selecting historical lexemes and demonstrate their communicative and aesthetic roles in literary discourse.